(untitled) - Taketani, Mitsuo (Singapore, 2001)
This text analyzes the intricate logical process through which the quantum theory was developed, and shows that the quantum mechanics thus established is governed by stereo-structural logic. The method of analysis is based on Mituo Taketani's three-stage theory of scientific cognition, which was presented and developed in close connection with Yukawa's theory of the meson. According to the three-stage theory, scientific cognition proceeds through a series of coiling turns of the phenomenological, substantialistic and essentialistic stages. The old quantum mechanics is shown to be in a substantialistic stage, followed by the quantum mechanics in the corresponding essentialistic stage.
Keywords: Cơ học lượng tử,Quantum theory